2021
DOI: 10.1186/s41231-021-00089-y
|View full text |Cite
|
Sign up to set email alerts
|

Effect of hydrolysable tannin on nutrient intake obesity and other associated metabolic risk factors in polycystic rats

Abstract: Background Food intake and eating behavior are two important risk factors that lead to obesity and other associated metabolic and reproductive disorders like polycystic ovarian syndrome (PCOS). Most of the phytonutrients like hydrolysable tannin (HT) have the ability to reduce the nutrient intake that might be a suitable remedy for weight management of females in their reproductive age. Therefore, the present research is aimed to find out the effect of HT on nutrient intake, weekly body weight,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…Previously, increased oxidative status has been determined in the systemic circulation and follicular fluids of PCOS rats [ 39 ]. Imbalanced reproductive hormones and insulin resistance is the key characteristics in PCOS patients and were responsible for the imbalance in energy homeostasis, development of adiposity, and weight gain [ 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…Previously, increased oxidative status has been determined in the systemic circulation and follicular fluids of PCOS rats [ 39 ]. Imbalanced reproductive hormones and insulin resistance is the key characteristics in PCOS patients and were responsible for the imbalance in energy homeostasis, development of adiposity, and weight gain [ 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…Further, tannins are proven to increase the level of satiety and decrease the frequency of voluntary food intake. In reality, tannin exposure leads to an improvement in lipid profile [46]. An HFD load in the long term could result in increased plasma concentrations of TG, LDL, non-HDL, and total cholesterol [47].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that tannins could lower cholesterol, triglyceride, LDL, and increase HDL levels in obese rats. In addition, tannins could reduce ghrelin activity, which regulates hunger to regulate food intake and reduce body weight (Manzoor et al, 2021;Panche et al, 2016). Alkaloid mechanisms in losing weight include suppressing lipogenesis, suppressing leptin expression, and sterol regulatory element-binding protein-1c (SREBP-1c).…”
Section: Resultsmentioning
confidence: 99%